Research progress of knee fibrosis after anterior cruciate ligament reconstruction - Liang, YangYang; Zhang, QingQing; Fan, YouFei (Frontiers in Pharmacology, 2024)
Anterior cruciate ligament (ACL) injury is a common sports injury, and ACL reconstruction is an effective surgery for this trauma. Most cases gain good recovery after surgery, while some patients may experience knee stiffness, which is characterized by joint fibrosis, leading to reduced joint mobility, pain, and dysfunction. Currently, various research studies have been conducted to unveil the mechanisms underlying this condition, identifying pre-, intra-, and post-operative risk factors, and testify the efficacy of different therapeutic methods against it. In this review, we summarize the current progress regarding the advancements in knee fibrosis after ACL reconstruction. The risk factors associated with knee fibrosis are systematically delineated, accompanied by an evaluation of the efficacy of various treatment modalities for both the prevention and mitigation of fibrosis. Furthermore, recommendations for future research directions are proposed, offering a foundational basis for subsequent investigations.